2021
DOI: 10.1177/1049732320983788
|View full text |Cite
|
Sign up to set email alerts
|

Managing Strong Emotions: Nurses’ Recognition and Responses to Personal Emotions When Approaching Parents With Cancer and Their Dependent Children

Abstract: Care for sick parents and their dependent children (<18 years) has become a pertinent issue in health care. Nurses play an important role in caring for parents with cancer as well as their children. By utilizing a constructivist grounded theory approach, the aim of this study was to expand the research-based knowledge of nurses’ experiences of personal emotions in this research field and to develop a subsequent explanatory theory extending the existing concept of emotional labor. Interviews with 12 nurses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Despite the emotional burden practitioners often experience, sufficient training, supervision, and support have been found to alleviate this burden and improve the overall quality of care provided (Hagen et al, 2017;Hansson & Markström, 2014;Marzano et al, 2016;Rothes et al, 2014;Takahashi et al, 2011). These findings are reinforced in work focused on practitioners approaching parents with cancer, in which practitioners experienced a high emotional burden but found that regulating and processing strategies greatly alleviated this process (Tafjord, 2021). Training and clinical supervision and support are integral to equipping practitioners with the skills to manage the emotional burden of working with suicidal clients, as well as setting boundaries to maintain their own mental health and avoid burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the emotional burden practitioners often experience, sufficient training, supervision, and support have been found to alleviate this burden and improve the overall quality of care provided (Hagen et al, 2017;Hansson & Markström, 2014;Marzano et al, 2016;Rothes et al, 2014;Takahashi et al, 2011). These findings are reinforced in work focused on practitioners approaching parents with cancer, in which practitioners experienced a high emotional burden but found that regulating and processing strategies greatly alleviated this process (Tafjord, 2021). Training and clinical supervision and support are integral to equipping practitioners with the skills to manage the emotional burden of working with suicidal clients, as well as setting boundaries to maintain their own mental health and avoid burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Parents play an essential role in assessing the atmosphere and emotions within it. Research shows that large spaces can allow learners to work individually and reduce noise (Tafjord, 2021). This suggests that flexibility in physical space can lead to positive interactions between teachers and learners.…”
Section: Spatial Organization and Arrangementmentioning
confidence: 99%
“…Parents play an essential role in assessing the atmosphere and emotions within it. Research shows that large spaces can allow learners to work individually and reduce noise (Tafjord, 2021). This suggests that flexibility in physical space can lead to positive interactions between teachers and learners (Higgins et al, 2005).…”
Section: Spatial Organization and Arrangementmentioning
confidence: 99%